2014
DOI: 10.1093/trstmh/tru160
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors related to intestinal parasites among children in Department of Rio San Juan, Nicaragua

Abstract: Government efforts should be focused on controlling the risk factors associated with these enteroparasites, with health education programmes in rural areas of Nicaragua.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
5
10
1
3
Order By: Relevance
“…We found no significant association between behavioural, service-related, and environmental factors in this study area. This is contrary to other studies [15,21,30,31]. In the current study, the socioeconomic characteristics of an individual were the main drivers of worm infestation.…”
Section: Discussioncontrasting
confidence: 99%
“…We found no significant association between behavioural, service-related, and environmental factors in this study area. This is contrary to other studies [15,21,30,31]. In the current study, the socioeconomic characteristics of an individual were the main drivers of worm infestation.…”
Section: Discussioncontrasting
confidence: 99%
“…36,37 Globally, earlier investigations demonstrated several risk factors for the high prevalence and incidence of IPIs including poor sanitation, low family income, poor personal hygiene, untreated water supply, low level of self and parental education, eating unwashed vegetables, contact with animals and contaminated soils. 9,38,39 In our study, univariate analysis showed that increasing in age, rural and farmer being are potential risk factor to acquisition of IPIs in north of Iran. However, none of the variables were statistically significant in logistic regression analysis.…”
Section: Discussionsupporting
confidence: 49%
“…A total of 30 helminth-only [38,39,4144,47,48,5156,58,63,64,68,70,72,73,7679,8184] and 18 helminth-intestinal protozoa [47,53,86–92,95,97,101,102,110,112,113,116,119] studies provided categorical data concerning the number of parasites in each host and were evaluated using the Janovy model. Twenty studies demonstrated significantly different observed frequency distributions of infection compared to the frequency of host infection expected in each host class if infections were independent events for helminth-only studies, while ten studies demonstrated significant differences in these distributions for helminth-intestinal protozoa studies (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%